Impact of neighborhood safety on adolescent physical activity in Saudi Arabia: gender and socio-economic perspectives - Abdullah Addas; Abdullah Addas (Frontiers in Public Health)
Background and objectivesAdolescent physical activity is a critical determinant of long-term physical and mental health. However, the factors influencing activity levels remain underexplored in rapidly urbanizing regions such as Saudi Arabia, where changing built environments pose unique challenges.MethodsThis study examined the relationship between neighborhood safety perceptions and physical activity levels among 1,500 adolescents aged 14–17 years in the cities of Riyadh, Jeddah, and Dammam, representing a mix of urban and suburban settings. This study used a cross-sectional design with data collected through a validated self-reported questionnaires and interviews; the data were analyzed through multivariate regression.ResultsThe results indicate that adolescents who perceived higher traffic-related safety concerns engaged in 30% less physical activity compared to those in safer neighborhoods (p < 0.01). Female adolescents were 20% more likely than male adolescents to report safety concerns (p < 0.05), while those residing in villas engaged in 15% more physical activity than their peers living in flats (p < 0.05).ConclusionsThese findings underscore the significant role of neighborhood safety in shaping adolescent health behaviors, particularly regarding traffic management and accessibility. These results contribute to the growing evidence regarding the influence of built environments on youth health and wellbeing in rapidly urbanizing regions. The study offers actionable policy recommendations for urban planners and public health officials to create safer, more inclusive environments that encourage physical activity, especially among female adolescents. Future research should adopt longitudinal designs and incorporate objective measures, such as wearable activity trackers, to assess the long-term impact of neighborhood safety interventions on adolescent health outcomes.